Pelepasan Ion Kobalt dari Aloi CoCr L605 pada Saliva Asam - Hilda Mutia Hanum; Widowati Siswomihardjo; Siti Sunarintyas (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2019)
CoCr has high mechanical properties but may release ion in an acidic environment as in the oral cavity. Cobalt (Co) ion can release from CoCr alloy if such material is immersed in acidic environment. This situation may lead to several consequences including allergies and oral lesions. The aim of this research was to determine the influence of pH degree on acidic saliva to the Co ion release concentration of CoCr L605 alloy. This research used CoCr L605 alloy and artificial saliva. Twelve samples of CoCr L605 metal plates were made into (10x10x1.5) mm size. The samples were divided into three groups; each group immersed in 20 ml of artificial saliva for 14 days, 37o C. The pH variables for the groups are 3, 5 and 7. Co ion released was measured by Atomic Absorption Spectroscopy (AAS). Data analysis was performed by one-way ANOVA (Analysis of Variance). The result showed that the mean of concentration value of Co ion released for group pH of 3, 5 and 7 were (3.0970±0.612)ppm; (2.0250±0.609) ppm; and 0.000 ppm respectively. One-way ANOVA showed that pH degree of acidic saliva significantly influenced by the Co ion release concentration (p<0.05). LSD test showed a significant difference between groups. The conclusion of this research was the less pH degree of saliva, the concentration of Co ion released of CoCr L605 alloy was higher.